Pemanfaatan Media Audio Pembelajaran Permainan Tradisional Anak Nusantara (Permata Nusantara) Untuk Meningkatkan Sosial Emosional Anak Usia Dini Di TK ABA Among Putro Kadirojo Bantul - Suryaningsih, Any (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
This study aims to improve children's emotional emotional health through the use of Permata Nusantara audio media at ABA Kindergarten Among Putro Kadirojo Bantul. This research uses Classroom Action Research. The subjects in this study were B2 early childhood and there were 18 children. Data collection methods used observation, interviews, and documentation. Data collection instruments in the observation guidelines and interview guidelines. Data were analyzed descriptively quantitatively. Indicator of success if the social emotional value of KKM = 76%. Social emotional abilities can be improved by traditional audio learning media for Indonesian archipelago children (PERMATA NUSANTARA) by using research steps, namely planning, action, observation, and reflection. The results obtained from pre-action emotional social abilities 53,3% (less) then increased to 78,1% (good) in the first cycle and increased to 96,8% (good) in the second cycle.